Tanggung Jawab Negara Terhadap Eksistensi Masyarakat Pemukim Di Atas Air (Studi Kasus: Suku Bajo Desa Samabahari, Kabupaten Wakatobi) - Nurahmani, Aditya, AN (Jurnal Hukum & Pembangunan, 2024)
The settler communities on the water are like the Bajo tribe, they have had a tradition of living on the water and in coastal areas for generations even before Indonesia became independent. The settler communities on the water have faced various problems such as legal certainty for settlements, threats of eviction, difficulty in accessing clean water and acts of discrimination. In this research, there are 2 (two) things to be studied, firstly what is the position of the settler community on the water in terms of the principle of common property resources in marine management and secondly what is the state's responsibility in protecting the existence of the Bajo Tribe Community in Samabahari Village, Wakatobi Regency. Using sociological juridical methods, the author concludes: Firstly, the principle of common property resources in marine space management does not mean prohibiting settler communities on the water from carrying out life on the waters/coasts. These principles must be defined contextually and take into account the socio-cultural conditions of society. Second, the state has the responsibility to provide protection for the settler community on water through legal certainty of land rights, ease of use of marine space and guaranteed provision of clean water. Keywords: Sea, Settlers on the Water, Bajo Tribe